Stonemill and Bhakti - Poitevin, Guy,Rairkar, Hema (D.K. Printworld, 1996)
Study on devotion (Bhakti) in Marathi poetry recited, while in work, by the women peasants of Pune District.
Keywords: Bhakti; Bhakti in literature; Devotional literature; Marathi; Women peasants; Bäuerin; Literatur